LEGAL ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC CERTIFICATES IN LAND ADMINISTRATION TO SUPPORT SMART LAND GOVERNANCE (RESEARCH STUDY AT THE TANJUNGPINANG CITY LAND OFFICE) - Sella Natasha; Laily Washliati; Maniah (CV. RADJA PUBLIKA, 2025)
The digitization of land administration through the implementation of electronic certificates is part of the government's efforts to realize smart land governance in Indonesia. The city of Tanjungpinang was chosen as the location for this study because it is one of the regions that has implemented the electronic certificate program in accordance with Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities. However, implementation in the field still faces a number of obstacles, both in terms of regulations, technicalities, and the readiness of human resources and service users. This study aims to analyze: (1) legal regulations regarding electronic certificates in land administration in Tanjungpinang City, (2) the implementation of electronic certificates in land administration practices, and (3) the contribution of the application of electronic certificates to increasing transparency, efficiency, and accountability of land governance based on smart land governance. The research method used is a descriptive qualitative approach with data collection techniques through literature study, in-depth interviews, observation, and documentation. The research subjects include officials and employees of the Tanjungpinang City Land Office, notary staff, and users of electronic land services. The analysis was conducted by comparing the regulatory framework with the reality of implementation in the field. The results show that although the legal basis for the implementation of electronic certificates is clear, its implementation still faces significant challenges, including limited technological infrastructure, low digital literacy among the public, lack of inter-agency integration, and dualism between manual and electronic procedures. Nevertheless, electronic certificates are considered to have great potential in improving the transparency, efficiency, and accountability of land governance. In order to achieve the goal of smart land governance, it is necessary to strengthen operational regulations, increase human resource capacity, develop equitable digital infrastructure, and conduct intensive public outreach.